Comparative Study on Anumana and Inference of Hindu and Western Philosophy - Dongol, Nikhil (Kathmandu School of Law Review, 2018)
Philosophy is called darsanas in Sanskrit language. Hindu Philosophy is the group of darsanas that emerged in ancient Indian sub-continent which also includes present Nepal. It dates back as much earlier than the western philosophy. It includes two philosophies: Astika and Nastika. Astika includes 6 systems: Samkhya, Yoga, Nyaya, Vaisheshika, Mimamsa and Vedanta. Among them, Nyaya deals with logic and reasoning. According to Nyaya Philosophy, there are four means of valid reasoning (pramana) that, according to it, help one to release from suffering. They are: Perception, Inference (Anumana), Comparison and Testimony. Among them, this paper is going to illustrate on Anumana and Inference of two Philosophies and its types and kinds. It denotes the early civilizations and helps to identify how logic was developed in East as well as in the West. And it helps to distinguish how the conclusion was made on these two parts of the world. However, this article is limited to anumana of Nyaya philosophy while other 5 systems of Astika also contain anumana.